ANALISIS FAKTOR-FAKTOR WORK-LIFE BALANCE PADA PEGAWAI PT. INDUSTRI TELEKOMUNIKASI INDONESIA (PERSERO) BANDUNG - Pratiwi, Dewi Padmi; Silvianita, Anita (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2020)
Companies that manage their human resources professionally will create a balance of work life and personal lives of its employees. This happened at PT. INTI Bandung where the employees already feel a balance between work life and personal life. Thus, the authors conducted this study to determine the work-life balance factor and what was the most dominant factor in the employees of PT. INTI Bandung. The method used in this study is quantitative with descriptive analysis and factor analysis as well as the sampling method that is simple random sampling. The results showed the condition of work-life balance in PT. INTI Bandung has been balanced by proven by the results of the analysis of the questionnaire data that produced a value that reached 77.2%. While the results of the factor analysts indicate that there are four new factors formed, namely the first factor Management of the Work Environment with a contribution value of 32.70%, the second factor Time Management and Role with a contribution value of 13.01%, the third factor Work Time Flexibility and Stress Level with a contribution value of 10.02%, and a fourth factor, Corporate Support with a contribution value of 7.60%. Thus the most dominant work-life balance factor in PT. INTI Bandung is a factor in the Management of Work Environment with a contribution value of 32.70%